Optimizing Tofu Production with Contextual Learning and Linear Programming - Yulianto, Dwi; Juniawan, Egi Adha (IndoMath: Indonesia Mathematics Education, 2024)
The study of contextual learning implementation introduces mathematical concepts by linking the material with real-life situations or contexts in Rancamulya Village, West Java, commonly known as Tofu Village, where tofu is a staple food and an affordable source of nutrition favored by the wider community. Through research using linear programming simplex method, an optimal solution was found to maximize tofu production, achieving a maximum profit of Rp 1,480,000 with the production of 364 white and 182 yellow tofu boards. Seventy-two mathematics education students at La Tansa Mashir University, Rangkasbitung, conducted this project-based ethnomathematics study. The research employed an ethnographic approach with data collection techniques through observation, documentation, and interviews. Data analysis was performed using a mixed-method approach combining qualitative and quantitative methods. The quantitative data revealed a significant difference in mathematical critical thinking skills between the Problem-Based Learning (PBL) and Numbered Heads Together with Student-Constructed Criteria for Success (NHT-SCCS) learning models. Students taught with the PBL model demonstrated higher critical thinking skills compared to those using the NHT-SCCS model.